2007
DOI: 10.1002/mren.200600040
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Study of Multifunctional Initiators in Free Radical Polymerizations

Abstract: An overview of a systematic investigation of a tetrafunctional peroxide initiator's behaviour is presented. The study focuses on three main areas of research: kinetic experiments, polymer characterization and modelling efforts. The kinetic investigation compared the behaviour of the tetrafunctional initiator (JWEB50) to that of a monofunctional counterpart (TBEC) for a variety of monomers. Although higher rates of polymerization were generated with JWEB50 for all monomers investigated, switching from a mono‐ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
0
8
0
2
Order By: Relevance
“…Their study revealed that the initiator effect on molecular weight distribution was dependent upon the monomer type. Characterization analysis revealed that the existence of chain branching affected rheological properties of polymer samples . Also, Galhardo et al studied the effect of bifunctional initiators on vinyl acetate polymerization to produce branched polymer at lower temperature, but no branching was recorded for polystyrene produced with the same initiator.…”
Section: Introductionmentioning
confidence: 99%
“…Their study revealed that the initiator effect on molecular weight distribution was dependent upon the monomer type. Characterization analysis revealed that the existence of chain branching affected rheological properties of polymer samples . Also, Galhardo et al studied the effect of bifunctional initiators on vinyl acetate polymerization to produce branched polymer at lower temperature, but no branching was recorded for polystyrene produced with the same initiator.…”
Section: Introductionmentioning
confidence: 99%
“…There are a limited number of works dealing with the use of multifunctional initiators (i.e. initiators containing more than two labile groups per molecule) . Cerna et al studied the particular case of the bulk polymerization of St using a cyclic trifunctional peroxide initiator, the diethyl ketone triperoxide (DEKTP).…”
Section: Introductionmentioning
confidence: 99%
“…The authors prove that under specific experimental conditions narrow molecular weight distributions (MWDs) and polydispersities (PDIs) around 1.5 can be obtained. Scorah et al10 used a tetrafunctional initiator on conventional polymerization and proved that it is possible to produce polymers with different structures when compared to the ones produced using monofunctional initiator. Zhang and Zhang11 produced a star copolymer of styrene and butadiene using a multifunctional macromolecular initiator.…”
Section: Introductionmentioning
confidence: 99%